The Semantic Effect of the Qur’anic Readings in the Last Part of the Holy Qur’an - Abdur-Rasheed Mahmoud-Mukadam; Muhyideen Ademola Abdussalam (Cordova Journal : languages and culture studies, 2022)
The scholars had realized that Qur’anic readings –frequent and odd readings- have notable impact in enriching and diversity the meanings of Qur’anic verses. In the last part of the Holy Qur’an, there are readings worth studying in this kind of the research. This research will study (The semantic impact of Qur’an readings in the last part of the Holy Qur’an,). The study aims to highlight the value of readings in the multiplicity of meanings and detection of readings that carry semantic impact of in the last part. This research consists of five chapters, the first chapter is an introduction and a preface, and in the scond chapter, change of vocabularies, and in the third chapter, the change in form, and the fourth chapter, the change in syntax, and the fifth chapter consists of a conclusion containing the most important results and recommendations, followed by the list of references. The researcher used descriptive and analytic method and explained its steps in the introduction.